PKM Smart Village Melalui Pengelolaan Perpustakaan Desa Rintisan Berbasis Teknologi Informasi Di Desa Bantarsari Bogor - Kurnianingsih, Indah; Yugaswara, Heri; Suhaeri, Suhaeri; Wardiyono, Wardiyono; Rosini, Rosini (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The establishment of the Bantarsari village library is one of the objectives of the Community Partnership Program entitled PKM, an Information Technology-Based Enterprise Crystal GuavaVillage in Bantarsari Village, Rancabungur, Bogor, West Java. The purpose of establishing a village library is to improve the quality of human resources by providing printed and electronic information sources that are managed by the library by utilizing information technology. The method of implementing community service activities involves three stages: preparation, implementation, and evaluation that supports the Smart village concept. In the preparation phase which includes an analysis of the needs of the village library and procurement of collections following the information needs of the Bantarsari village community. Furthermore, at the implementation stage in the form of training on the management and utilization of information technology-based village libraries for village officials and some community members. At the evaluation stage, the service activity is in the form of monitoring community service activities and evaluating indicators of the achievement of activities. The results of the community service activities besides the availability of a physical library that provides sources of information according to the needs of the villagers are also available a school library management application based on the SchILS (School Integrated Library System) in which there is already a collection of electronic school books from the Ministry of Education and Culture of the Republic of Indonesia from elementary school level, middle, and high school. The system can be accessed free of charge by all Bantarsari villagers through mobile or computer media using the village intranet network.